1969
DOI: 10.1021/ja01045a043
|View full text |Cite
|
Sign up to set email alerts
|

Solvolysis rates and deuterium isotope effects in 2,2,2-trifluoroethanol-water mixtures

Abstract: 2,2,2-Trifluoroethanol (TFE)-water is a convenient solvent for the precise conductometric measurement of solvolysis rates. A comparison of results in TFE-water with those in ethanol-water gives a useful indication of the role of changing nucleophilicity in solvolysis reactions. It has been found that the a-and /3-deuterium effects in 1-phenylethyl chloride, which in ethanol-water are at or near a maximum characteristic of a limiting reaction, are not much changed in TFE-water. However, for /-butyl-d» chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…We adopt the same approach here in following a treatment proposed by Murr and Donnelly (41). Assume that a stepwise mechanism of minimal complexity can be represented by reaction [4]. If intimate ion pair 2 partitions between internal 1 2 3 return to 1 and irreversible dissociation to loose ion pair 3, such that k3 >> k-2, then the observed chlorine isotope effect is given by eqs.…”
Section: Isotope Effects In Multistep Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt the same approach here in following a treatment proposed by Murr and Donnelly (41). Assume that a stepwise mechanism of minimal complexity can be represented by reaction [4]. If intimate ion pair 2 partitions between internal 1 2 3 return to 1 and irreversible dissociation to loose ion pair 3, such that k3 >> k-2, then the observed chlorine isotope effect is given by eqs.…”
Section: Isotope Effects In Multistep Mechanismsmentioning
confidence: 99%
“…Kinetic (I), stereochemical (2), secondary a-and P-deuterium isotope effect (3,4), and carbon isotope effect (5-8) studies have been reported. Recent work has focussed on the generation and the fate of substituted 1-phenylethyl cations in solution as a function of their lifetimes (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorirle p-Methylbenzyl chloride has been extensively investigated both with regard to solvolytic activation parameters (5 -7) and precision Hdeuterium kinetic isotope effects (3,8). This compound was selected as a convenient refpr.cnce J:,,sletn for our studies.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, several k 40%EtOH /k 97%TFE values were reported for the proposed unimolecular S N 1 reaction or ionization pathway: the solvolyses of diphenyl chlorometane, 12,25 p-methoxybenzyl chloride, 12 cinnamyl chloride, 13 1-chloro-1-phenylethane, 23,26 4-chloro-4-methyl-2-pentyne, 22(a) trans-4-chloro-2-pentene, 22(a) tert-butyl chloride, 6(c),23 and 1-piperidinecarbonyl chloride 14 (See Table 3). Small values (k 40%EtOH / k 97%TFE = 0 to ~25) were observed due to the two solvents having the same Y Cl value, i.e., the same degree of solvent assistance for bond cleavage, but different nucleophilicity, Scheme 2 which provides a measure of the minimum extent of nucleophilic assistance.…”
Section: (G)6(h)9(a)2223mentioning
confidence: 99%